Medical Device Reliability and Measuring Instrument Specifications (Eurasian Journal of Engineering and Technology, 2024)
At work medicine of devices reliability and measure of tools descriptions order about information given. Electronic of components reliability high requirements provide main resources these sizes straight away work efficiency complete to be is to provide.